Late nineteenth-century Italy in Africa : the Livraghi Affair and the waning of civilizing aspirations - Bruner, Stephen C. (Cambridge Scholars Publishing, 2017)
"Civilizing Africa"--Bringing European institutions and society to Africa - was a common rationale for nineteenth-century European expansions into that continent. However, in March 1891 a news correspondent accused officials in Italy's Red Sea colony of having ordered, without trial, the secret and brutal killing of certain indigenous notables. A scandal erupted because the news contradicted civilizing expectations, portraying Italians rather than Africans as the barbarians. The press drove a public debate over the accusations, but the debate ultimately led to an unanticipated reversal: publi